Study on the Role of the Inclusion Complexes with 2-Hydroxypropyl-β-cyclodextrin for Oral Administration of Amiodarone - Andreea Creteanu; Daniela Pamfil; Cornelia Vasile; Gladiola Tantaru; Cristina Mihaela Ghiciuc; Lacramioara Ochiuz; Alina Ghilan; Ana Maria Macsim (International Journal of Polymer Science)
The aim of this study was to improve the solubility of amiodarone hydrochloride (AMD) and the drug release using its inclusion complexes with 2-hydroxypropyl-β-cyclodextrin (HP-β-CD). The inclusion complexes were prepared by coprecipitation and freeze-drying. The solubility enhancement of AMD/HP-β-CD inclusion complexes by 4–22 times was evaluated by the phase solubility method. The inclusion complexes were studied both in solution and in solid state by spectroscopic methods, dynamic light scattering (DLS) and zeta potential analysis, SEM, and DSC. The formulations of AMD/HP-β-CD inclusion complexes both as powdered form and as matrix tablets showed superior pharmacokinetic performance in improving loading and release properties in respect of those of the insoluble AMD drug. In vitro kinetic study reveals a complex mechanism of release occurring in three steps: the first one being attributed to a burst effect and the other two to different bonding existing in inclusion complexes. An in vivo test on matrix tablets containing Kollidon® and chitosan also reveals a multiple (at least two) peaks release diagram because of both structures of the inclusion complexes and also of different sites of absorption in biological media (digestive tract).